2016
DOI: 10.14743/apem2016.4.231
|View full text |Cite
|
Sign up to set email alerts
|

Effect of delayed differentiation on a multiproduct vendor-buyer integrated inventory system with rework

Abstract: This study explores the effect of delayed differentiation on a multiproduct vendor-buyer integrated inventory system with rework to identify its potential benefits and provide managers with in-depth information for operational decision-making. The main considerations of the proposed study include a multiproduct fabrication plan to increase machine utilization, a rework process to ensure product quality, and a multi-shipment policy to distribute the end products. In addition, these products sharing an intermedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…The results from three different options can help management in better decision making. Chiu et al (2016a) used mathematical modeling to explore a single-machine two-stage multiproduct vendorbuyer integrated inventory system with rework, wherein all common parts needed for all products are fabricated in stage one, and end products are produced sequentially under a common production cycle time policy in stage two, both on a single machine. Their objective was to cut down the system cost and reduce the production cycle time as compared to what was obtained from a single stage production system.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The results from three different options can help management in better decision making. Chiu et al (2016a) used mathematical modeling to explore a single-machine two-stage multiproduct vendorbuyer integrated inventory system with rework, wherein all common parts needed for all products are fabricated in stage one, and end products are produced sequentially under a common production cycle time policy in stage two, both on a single machine. Their objective was to cut down the system cost and reduce the production cycle time as compared to what was obtained from a single stage production system.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, they derived the closed-form optimal replenishment cycle time and delivery decisions and showed that their two-stage fabrication production system with delayed differentiation is considerably beneficial vis-à-vis single-stage scheme in cost saving and cycle time reduction. Chiu et al (2016c) further extended the same model of Chiu et al (2016a) with extra features on random scrap rates existence in both regular fabrication and rework processes for both common part's and end products' fabrication stages using single-machine production scheme. Prior literatures regarding different aspects of the postponement strategy used in multiproduct fabrication systems can also be found elsewhere (Gerchak and Henig, 1986;Lee, 1996;Swaminathan and Tayur, 1998;Graman and Magazine, 2002;Gupta and Benjaafar, 2004;Weber, 2008;Bernstein et al, 2011;Ferreira et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations